Urinary Tract Infections Caused by K. pneumoniae in Kidney Transplant Recipients – Epidemiology, Virulence and Antibiotic Resistance - Krawczyk, Beata; Wysocka, Magdalena; Michalik, Michał; Gołębiewska, Justyna (Frontiers in Cellular and Infection Microbiology, 2022)
Urinary tract infections are the most common complication in kidney transplant recipients, possibly resulting in the deterioration of a long-term kidney allograft function and an increased risk of recipient’s death. K. pneumoniae has emerged as one of the most prevalent etiologic agents in the context of recurrent urinary tract infections, especially with multidrug-resistant strains. This paper discusses the epidemiology and risk factors associated with urinary tract infections in kidney transplant recipients, multi-drug resistance of K. pneumoniae (ESBL, KPC, NDM), treatment and pathogenesis of K. pneumoniae infections, and possible causes of recurrent UTIs. It also addresses the issue of colonization/ becoming a carrier of K. pneumoniae in the gastrointestinal tract and asymptomatic bacteriuria in relation to a symptomatic UTI development and epidemiology.